Quality of life outcomes in people with Primary Biliary Cholangitis treated with obeticholic acid: results of a phase 4 real life observational trial. (March 2023) - Rollo, P.; D'Ovidio, E.; Bonaiuto, E.; Perini, L.; Pezzato, F.; Peviani, M.; Simionato, F.; Russo, F.P.; Floreani, A.; Cazzagon, N.
Abstract : Introduction: Primary biliary cholangitis (PBC) can be associated with impaired health-related quality of life (HRQoL) caused by symptoms, mainly pruritus and fatigue, and eventually depression.Treatment confidence strongly affects HRQoL in PBC, and UDCA has been reported to be a positive factor in enhancing trust therapy. No real-life data on this and HRQoL exist regarding obeticholic acid (OCA) second-line therapy. Aim: To assess the impact of OCA on biochemistry, patients' illness perception and HRQoL of PBC patients Methods: We designed a phase 4 observational open label study (Protocol AOP1515) and collected at baseline and every 6 months from starting OCA biochemistry, adverse events, reported symptoms and the results of following questionnaires: PBC-40, Fatigue Impact Scale(FIS), 5-D Itch scale, EuroQoL-5D-5L. Changes in symptoms after OCA introduction were assessed by Wilcoxon paired rank test. Results: Nineteen (60%) over 32 patients who started OCA treatment between March 2018 and April 2022 for insufficient response to UDCA agreed to participate. Median duration of OCA treatment was 32(15-53) months with no drug discontinuation due to adverse events. A decrease of alkaline phosphatase compared to baseline below 1.5xULN and 1xULN was observed in 47%, 67%, 64%, 67% and 16%, 21%, 35%, 17% patients at 6, 12, 18, 24 months, respectively. At the time of starting OCA, significant pruritus, fatigue, cognitive and social dysfunction, emotional impairment, and general symptoms were present in 5%, 32%, 11%, 53%, 37%, 21% patients, respectively. No significant aggravation of itch or other symptoms was observed after OCA introduction, except for a transient aggravation in emotional domain at 12 months (8[5-10] vs. 14[9-19], p=0.005). A trend over a significant reduction of fatigue evaluated by FIS at 36 months was observed (45[0-82] vs. 10.5[0-42], p=0.06). All patients reported a significant and persistent general improvement after OCA introduction. Conclusion: People with PBC and insufficient response to UDCA experienced a biochemical and subjective improvement after OCA introduction and no aggravation of objectively assessed HRQoL.